2021
DOI: 10.1111/vco.12755
|View full text |Cite
|
Sign up to set email alerts
|

SLUG is upregulated and induces epithelial mesenchymal transition in canine oral squamous cell carcinoma

Abstract: SLUG, encoded by the Snai2 gene, is known to play a role in epithelial-mesenchymal transition (EMT), which contributes to cell invasion and metastasis in some types of human carcinomas. However, the mechanisms and roles of EMT in canine squamous cell carcinoma (SCC) have not yet been elucidated. We have previously established canine oral SCC cell lines, including tonsillar SCC, and in this study, we evaluated the effects of SLUG on the phenotypes regarding EMT of canine SCC cells. First, immunohistochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These results suggest that the investigation of the EMT process in canine oral and cutaneous squamous cell carcinomas may allow a more accurate prediction of their biological behavior [ 285 ]. Another more recent study underlined the importance of SLUG in promoting migration and invasion through EMT induction in a canine oral squamous cell carcinoma cell line [ 286 ].…”
Section: An Overview Of Epithelial-to-mesenchymal Transition and Mese...mentioning
confidence: 99%
“…These results suggest that the investigation of the EMT process in canine oral and cutaneous squamous cell carcinomas may allow a more accurate prediction of their biological behavior [ 285 ]. Another more recent study underlined the importance of SLUG in promoting migration and invasion through EMT induction in a canine oral squamous cell carcinoma cell line [ 286 ].…”
Section: An Overview Of Epithelial-to-mesenchymal Transition and Mese...mentioning
confidence: 99%
“…This pattern is similar to that observed in Gu et al, where IHC indicated a higher SLUG expression in human breast carcinoma than in normal mammary gland tissue. In terms of oral squamous cell carcinoma (SCC), this pattern is slightly different from that in canine oral SCC studied by Noguchi et al, where SLUG expression is mainly observed in the nucleus and partly in the cytoplasm [ 20 ]. However, in human studies of oral SCC, SLUG expression was detected in 71% of tumor cell cytoplasm [ 15 ].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, high SLUG expression is associated with poor clinical outcomes in human gastric cancer [ 14 ], esophageal squamous cell carcinoma [ 15 , 16 ], colorectal carcinoma [ 17 ], lung adenocarcinoma [ 18 ], and prostate cancer [ 19 ]. To the best of our knowledge, SLUG has been studied only in association with canine oral squamous cell carcinoma [ 20 ] and melanoma in a mouse model [ 21 ]. Furthermore, human breast cancers are correlated with high SLUG expression.…”
Section: Introductionmentioning
confidence: 99%
“…Validation of the mechanisms involved in TSCC metastasis is required to improve the prognosis. This study revealed that miR-203 is downregulated in both TSCC and NTSCC and targets SLUG , which plays an important role in sustaining the mesenchymal phenotype, resulting in the suppression of the migration and invasion of TSCC cells but not those of oSCC cells ( 5 ).…”
Section: Discussionmentioning
confidence: 95%
“…EMT is regulated by mesenchymal transcription factors, such as zinc finger E-Box Binding Homeobox 1, TWIST, SNAIL, and SLUG ( 4 ). In our previous study, SLUG has been suggested to be upregulated in canine oral SCC and is associated with the migration and invasion of TSCC and NTSCC cells ( 5 ).…”
Section: Introductionmentioning
confidence: 99%